Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1186/1471-2288-14-23
|View full text |Cite
|
Sign up to set email alerts
|

Influences on recruitment to randomised controlled trials in mental health settings in England: a national cross-sectional survey of researchers working for the Mental Health Research Network

Abstract: BackgroundRecruitment to trials is complex and often protracted; selection bias may compromise generalisability. In the mental health field (as elsewhere), diverse factors have been described as hindering researcher access to potential participants and various strategies have been proposed to overcome barriers. However, the extent to which various influences identified in the literature are operational across mental health settings in England has not been systematically examined.MethodsA cross-sectional, onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 9 publications
(18 reference statements)
2
51
0
Order By: Relevance
“…For example, time‐consuming project‐related activities that take place immediately after recruitment, such us arranging pathology rather than taking blood samples by a clinical nurse and contacting pharmacy staff to arrange either placebo or the medicine at some sites rather than having them on site, may also influence clinicians’ decision to avoid recruitment as a matter of saving time for their clinical work. Concurrent recruitment to other studies at the same site should also be considered …”
Section: Discussionmentioning
confidence: 99%
“…For example, time‐consuming project‐related activities that take place immediately after recruitment, such us arranging pathology rather than taking blood samples by a clinical nurse and contacting pharmacy staff to arrange either placebo or the medicine at some sites rather than having them on site, may also influence clinicians’ decision to avoid recruitment as a matter of saving time for their clinical work. Concurrent recruitment to other studies at the same site should also be considered …”
Section: Discussionmentioning
confidence: 99%
“…In some instances, clinicians do not know the client sufficiently well to make an informed judgement about non-maleficence and beneficence, key principles in medical bio-ethics (Beauchamp & Childress, 2001). Research shows that gatekeepers having protected time to undertake research activity enhances access to potential participants (Borschmann et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Research has identified a wide range of factors influencing recruitment in mental health randomised controlled trials (RCT) (Borschmann et al, 2014). Low recruitment This is an Open Access article distributed under the terms of the Creative Commons Attribution-NonCommercial-NoDerivatives License (http:// creativecommons.org/licenses/by-nc-nd/4.0/), which permits non-commercial re-use, distribution, and reproduction in any medium, provided the original work is properly cited, and is not altered, transformed, or built upon in any way.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations